(1‐aryloxy‐2‐hydroxypropyl)‐phenylpiperazine derivatives suppress Candida albicans virulence by interfering with morphological transition. Issue 6 (17th September 2018) - Zhao, Shuo; Huang, Jun‐Jun; Sun, Xiuyun; Huang, Xiaorong; Fu, Shuna; Yang, Liang; Liu, Xue‐Wei; He, Fei; Deng, Yinyue
Summary: Clinical treatment of Candida albicans infections has become more difficult due to the limited development of antifungal agents and the rapid emergence of drug resistance. In this study, we demonstrate the synthesis of a series of piperazine derivatives and the evaluation of their inhibitory activity against C. albicans virulence. Thirty‐four (1‐aryloxy‐2‐hydroxypropyl)‐phenylpiperazine derivatives, including 25 new compounds, were synthesized and assessed for their efficacy against the physiology and pathogenesis of C. albicans . Several compounds strongly inhibited the morphological transition and virulence of C. albicans cells, although they did not influence the growth rate of the fungal pathogen. A leading novel compound, (1‐(4‐ethoxyphenyl)‐4‐(1‐biphenylol‐2‐hydroxypropyl)‐piperazine), significantly attenuated C. albicans virulence by interfering with the process of hyphal development, but it showed no cytotoxicity against human cells at a micromolar level. These findings suggest that (1‐aryloxy‐2‐hydroxypropyl)‐phenylpiperazine derivatives could potentially be developed as novel therapeutic agents for the clinical treatment of C. albicans infections by interfering with morphological transition and virulence. Abstract : Our study described the synthesize and screen of a series of novel piperazine derivatives for their activity to block hyphae formation and virulence of Candida albicans . We have identified several derivatives remarkably attenuated C. albicans virulence by inhibiting the hyphae formation and biofilm formation, but they did not influence the growth rate of the fungal pathogen. In general, the specific significance of our findings is the high activity of these compounds in attenuation of C. albicans virulence but not killing of the fungal pathogen cells, which blocks the rapid emergence of drug resistance.